Heterogeneous Fenton Reaction Enabled Selective Colon Cancerous Cell Treatment. Issue 1 (December 2018) - Lee, Kuan-Ting; Lu, Yu-Jen; Chiu, Shao-Chieh; Chang, Wen-Chi; Chuang, Er-Yuan; Lu, Shih-Yuan
Abstract A selective colon cancer cell therapy was effectively achieved with catalase-mediated intra-cellular heterogeneous Fenton reactions triggered by cellular uptake of SnFe2 O4 nanocrystals. The treatment was proven effective for eradicating colon cancer cells, whereas was benign to normal colon cells, thus effectively realizing the selective colon cancer cell therapeutics. Cancer cells possess much higher innate hydrogen peroxide (H2 O2 ) but much lower catalase levels than normal cells. Catalase, an effective H2 O2 scavenger, prevented attacks on cells by reactive oxygen species induced from H2 O2 . The above intrinsic difference between cancer and normal cells was utilized to achieve selective colon cancer cell eradication through endocytosing efficient heterogeneous Fenton catalysts to trigger the formation of highly reactive oxygen species from H2 O2 . In this paper, SnFe2 O4 nanocrystals, a newly noted outstanding paramagnetic heterogeneous Fenton catalyst, have been verified an effective selective colon cancerous cell treatment reagent of satisfactory blood compatibility.